Genetic Variations in the Dopaminergic Reward System Are Associated with Exercise Reinforcement (P16-013-19) - Flack, Kyle (Curr Dev Nutr, 2019)
OBJECTIVES: This study tested whether genotypes previously identified as moderators of other reinforcing behaviors, such as eating and drug abuse, also influence exercise reinforcement and the choice to exercise, measured as the reinforcing value of exercise relative to sedentary activities (screen time, reading, etc.). Linking specific genetic signatures of central mechanisms of reinforcement with an individual's exercise reinforcement has yet to be investigated and may uncover central mechanisms that underlie individual differences in exercise motivation, usual exercise behavior and long-term exercise adherence. Since preference and tolerance for exercise intensity influences exercise reinforcement, genetic contributions of these individual characteristics were also evaluated. METHODS: Men (n = 51) and women (n = 127) were measured for the reinforcing value of exercise relative to sedentary activities (RRV(exercise)), minutes of usual moderate-to-vigorous physical activity (MVPA), and completed the Preference for and Tolerance of the Intensity of Exercise Questionnaire. Participants provided a blood sample for genotyping of 23 SNPs previously identified to influence central dopamine release/uptake, reinforcement, or physical activity behaviors. ANOVA analysis determined differences in RRV(exercise), preference, and tolerance among genotypes and linear regression analysis controlling for age, sex, and MVPA determined if genotype predicted RRV(exercise), and preference/tolerance for exercise intensity. RESULTS: Having at least one copy of the G allele for the DRD2/ANKK1 polymorphism (rs1800497) confers greater RRV(exercise) by increasing receptor binding or expression of the dopamine D2 receptor. Greater tolerance for exercise intensity was observed among those homozygous for the T allele for the CNR1 polymorphism (rs6454672), had at least one copy of the G allele for the GABRG3 polymorphism (rs8036270) and had at least one copy of the T allele for the LPR polymorphism (rs12405556) by influencing pain neurotransmission and leptin receptor binding. CONCLUSIONS: Similar to other reinforcing behaviors, there is a genetic contribution to exercise reinforcement and tolerance for exercise intensity. FUNDING SOURCES: USDA, Agricultural Research Service, Project 3062-51000-051-00D.